Magnetizability of doublet radicals using fock space multi-reference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2009)
In this article, we report the first implementation of the recently developed Fock space multi reference Coupled cluster (FSMRCC) response approach for magnetizabilities. The FSM-RCC treats dynamic and static correlation in a very extensive manner. We report pilot application of the diarnagnetizability of NO, NO2, OH, and BH2 radicals. We also report preliminary applications of the paramagnetic magnetizability of the NO radical. Standard atom-centered Gaussian basis functions have been used, and this allowed US to Study the gauge dependence of the magnetizabilities. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 109: 2191-2198, 2009
Keywords: Fock space; magnetizability; multireference